Effect of Plant Growth-Promoting Bacteria on Biometrical Parameters and Antioxidant Enzymatic Activities of Lupinus albus var. Orden Dorado Under Mercury Stress - Robas Mora, Marina; Jiménez Gómez, Pedro Antonio; González Reguero, Daniel; Probanza Lobo, Agustín (Frontiers in Microbiology, 2022)
Heavy metal contamination of soils is a large-scale environmental problem. It leads to significant disqualification of the territory, in addition to being a source of potential risk to human health. The exposure of plants to mercury (Hg) generates responses in its growth and itsoxidative metabolism. The impact of increasing concentrations of Hg on the development of Lupinus albus var. Orden Dorado seedlings has been studied, as well as the plant response to the maximum concentration of Hg that allows its development (16 µg.mL-1). Result shows that only the inoculum with plant growth promoting bacteria (PGPB) allows the biometric development of the seedling (root length, weight and number of secondary roots) and prevents the toxic effects of the heavy metal from aborting the seedlings. Specifically, treatments with strains 11, 20 (Bacillus toyonensis), 48 (not determined) and 76 (Pseudomonas syringae) are interesting candidates for further PGPB-assisted phytoremediation trials as they promote root biomass develoment, through their PGPB activities. The plant antioxidant response has been analyzed by quantifying the catalase (CAT), superoxide dismutase (SOD), ascorbate peroxidase (APX) and glutathione reductase (GR) enzyme activity in the root, under 16 µg.mL-1 of HgCl2 and different PGPB treatments. Results show that, although Hg stress generally induces enzyme activity, strains 31 and 69I (Pseudomonas corrugata) and 18 and 43 (Bacillus toyonensis) can keep SOD and APX levels close to those found in the control without Hg (p-value < 0.01). Strain 18 also shows a significant reduction of GR to control levels without Hg. The present work demonstrates the benefit of PGPB treatments in situations of high Hg stress. These findings may be a good starting point to justify the role of PGPB naturally isolated from bulk soil and from the rhizosphere of plants subjected to high Hg pressure in plant tolerance to such abiotic stress conditions. More studies will be needed to discover the molecular mechanisms behind the phytoprotective role of the strains with the best results, to understand the complex plant-microorganism relationships, in order to find effective and lasting symbioses useful in bioremediation processes.